In the verge of coronavirus pandemic, we are providing FREE access to our entire Online Curriculum to ensure Learning Doesn't STOP!

Problems On Doing Geometry With Complex Numbers

Go back to  'Complex Numbers'

Example - 37

If \(z{_1}\text{ and}\;z{_2}\)  are fixed and \(z\) satisfies

\[|z - {z_1}{|^2} + |z - {z_2}{|^2} = k,\]

find the possible values of  \(k \) so that this equation represents a circle.

Solution: Let us try to reduce (simplify) this equation

\[\begin{align}&\qquad \;\;|z - {z_1}{|^2} + |z - {z_2}{|^2} = k\\ &\Rightarrow \quad 2|z{|^2} - 2{\mathop{\rm Re}\nolimits} (z{{\bar z}_1} + z{{\bar z}_2}) + |{z_1}{|^2} + |{z_2}{|^2} = k\\ &\Rightarrow \quad |z{|^2} - {\mathop{\rm Re}\nolimits} \left( {z({{\bar z}_1} + {{\bar z}_2})} \right) = \frac{1}{2}\left( {k - |{z_1}{|^2} - |{z_2}{|^2}} \right)\end{align}\]

Careful thinking will show that the left hand side can be transformed into a perfect square with the following manipulation.

Thus, the centre is \(\begin{align}\,{z_0} = \frac{{{z_1} + {z_2}}}{2}\end{align}\) and the radius is \(\begin{align}\frac{1}{2}\sqrt {2k - |{z_1} - {z_2}{|^2}} .\end{align}\) For the radius to be defined the condition that \(k\) must satisfy is

\[k > \frac{1}{2}|{z_1} - {z_2}{|^2}\]

These are the possible values of \(k.\)

Example - 38

Let \(\bar bz + b\bar z = c,\,\,b \ne 1\) be a line in the complex plane. If a point \(z{_1}\)  is the reflection of a point \(z{_1}\) through the line, show that \(c = {\bar z_1}b + {z_2}\bar b,\)

Solution:

From the figure, it is obvious that the midpoint of \(AB\) must lie on the given line, i.e, \(\begin{align}&\frac{{{z_1} + {z_2}}}{2}\end{align}\) should satisfy the equation of the line. Also, \(AB\) must be perpendicular to the given line, i.e the complex slopes of \(AB\) and the given line must add to 0.

\[\begin{align} &\Rightarrow \,\,\,\bar b\left( {\frac{{{z_1} + {z_2}}}{2}} \right) + b\left( {\frac{{{{\bar z}_1} + {{\bar z}_2}}}{2}} \right) = c\,\,\,\,\,\,\,...{\text{ }}\left( 1 \right) \\\\ &\text{and}\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\frac{{{z_1} - {z_2}}}{{{{\bar z}_1} - {{\bar z}_2}}} + \left( {\frac{{ - b}}{{\bar b}}} \right) = 0 \\\\&\Rightarrow \,\,\,\bar b\left( {{z_1} - {z_2}} \right) - b\left( {{{\bar z}_1} - {{\bar z}_2}} \right) = 0\,\,\,\,\,\,\,\,\,...{\text{ }}\left( 2 \right)\\\\& 2 \times \left( 1 \right) - \left( 2 \right)\,\,\,{\text{gives us the required relation.}}\\\end{align} \]

Example - 39

Find the circumcenter of the triangle whose vertices are given by the complex numbers \(z{_1}{\rm{ }},z{_2}{\rm{\;and\; }}z{_3}{\rm{ }}.\)

Solution:

We have to find \(z,\) the circumcenter \(O\) of triangle \(PQR.\) By virtue of being the circumcenter, \(z\) is equidistant from \(z{_1}{\rm{ }},z{_2}{\rm{\;and\; }}z{_3}{\rm{ }}.\) Therefore,

\[\begin{align}&\qquad\qquad\left| {z - {z_1}} \right| = \left| {z - {z_2}} \right| = \left| {z - {z_3}} \right|\\ &\Rightarrow \,\,\,(z - {z_1})(\bar z - {{\bar z}_1}) = (z - {z_2})(\bar z - {{\bar z}_2}) = (z - {z_3})(z - {{\bar z}_3})\\\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,&\qquad\qquad\underbrace {\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}_{{\rm{Equality}}\,{\rm{A}}}\,\,\;\;\;\underbrace {\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}_{{\rm{Equality B}}}\\ \end{align}\]

\(\Rightarrow \) From the first two terms in the equality above (Equality \(A\)) we get:

\[\begin{gathered} z\, - z{{\bar z}_1} - {z_1}\bar z + {z_1}{{\bar z}_1} = z\, - z{{\bar z}_2} - {z_2}\bar z + {z_2}{{\bar z}_2} \hfill \\\Rightarrow \,\,\,\bar z({z_2} - {z_1}) = z({{\bar z}_1} - {{\bar z}_2}) + {\left| {{z_2}} \right|^2} - {\left| {{z_1}} \right|^2}\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,...\left( 1 \right) \hfill \\\end{gathered} \]

Similarly, from equality \(B,\) we get

\[\bar z({z_3} - {z_2}) = z({\bar z_2} - {\bar z_3}) + {\left| {{z_3}} \right|^2} - {\left| {{z_2}} \right|^2}\,\,\,\,\,\,\,\,\,...\left( 2 \right)\]

Dividing (1) by (2), we get :

\[\frac{{{z_2} - {z_1}}}{{{z_3} - {z_2}}} = \frac{{z({{\bar z}_1} - {{\bar z}_2}) + {{\left| {{z_2}} \right|}^2} - {{\left| {{z_1}} \right|}^2}}}{{z({{\bar z}_2} - {{\bar z}_3}) + {{\left| {{z_3}} \right|}^2} - {{\left| {{z_2}} \right|}^2}}}\]

Solving for \(z,\) we get

\[z = \frac{{{{\left| {{z_1}} \right|}^2}({z_2} - {z_3}) + {{\left| {{z_2}} \right|}^2}({z_3} - {z_1}) + {{\left| {{z_3}} \right|}^2}({z_1} - {z_2})}}{{{{\bar z}_1}({z_2} - {z_3}) + {{\bar z}_2}({z_3} - {z_1}) + {{\bar z}_3}({z_1} - {z_2})}}\]

Example - 40

\({z_1},\;{z_2}\;{\rm{and}}\;{z_3}\) are three points on a circle centered at the origin. A point \(z\) is chosen on the circle such that the line joining \(z\) and \({z_1}\) is perpendicular to the line joining \({z_2}\) and \({z_3}\) . Show that \(z{z_1} + {z_2}{z_3} = 0\)

Solution:

We observe \(\theta  = \phi \) that, because of the perpendicularity of the two secants.

Now \(\angle \,SOR + \angle SOQ - \angle SOP = \pi \) , (by using the fact that \(\theta  = \phi \) ). Therefore,

\[\begin{align}& \qquad\;\; \left( {\arg \left( {{z_3}} \right) - \arg (z)} \right) + \left( {\arg \left( {{z_2}} \right) - \arg (z)} \right) - \left( {\arg \left( {{z_1}} \right) - \arg (z)} \right) = \pi \\ &\Rightarrow \quad \arg \left( {{z_3}} \right) + \arg \left( {{z_2}} \right) = \pi + \arg \left( {{z_1}} \right) + \arg \left( z \right)\\ &\Rightarrow \quad \arg \left( {{z_2}{z_3}} \right) = \pi + \arg \left( {z{z_1}} \right)\\ &\Rightarrow \quad {z_2}{z_3} = - z{z_1} \Rightarrow \quad z{z_1} + {z_2}{z_3} = 0\end{align}\]

TRY YOURSELF - IX

Q. 1 Find the real slopes of the following lines

(a) \(iz - i\bar z + 1 = 0\)

(b) \(\omega z + {\omega ^2}\bar z + 1 = 0\)

(c) \({e^{i\frac{\pi }{4}}}z + {e^{ + \frac{\pi }{4}}}\bar z = 0\)

(d) \(3z + 3\bar z + 2 = 0\)

Q. 2 Write the complex forms for the following lines

(a) \(x + y + 1 = 0\)

(b) \(\sqrt 3 x - y + 1 = 0\)

(c) \(x = 1\) (d) y = 1

Q. 3 Consider a point  \(z{_0}\) on the circle \(|z|\; = r\) . What will be the equation of the tangent at \(z{_0}\) ?